Kitab Al-Risalah Imam Al-Syafi’i - Salmah Intan (Universitas Islam Negeri Alauddin, 2011)
Imam Syafi’i as one of Islamic school founder has codificated an Islamic law philosophical formulation that was documented in a book named Ar-Risalah. This book contains a very detailed formulation of Islamic law philosophy. It envolves the global and general formula that can become a handbook for Moslem to know the law of Islam. The law source disclosed by Syafi’i refered to Al-Quran and Hadis. By this book, a faqih (an expert in Islamic law) can consider law conclution and decide a religious code in accordance with prophet’s teaching.